Galaxy And Mass Assembly (GAMA): gas fuelling of spiral galaxies in the local Universe II. – direct measurement of the dependencies on redshift and host halo mass of stellar mass growth in central disc galaxies. Issue 1 (16th March 2018) - Grootes, M W; Dvornik, A; Laureijs, R J; Tuffs, R J; Popescu, C C; Robotham, A S G; Liske, J; Brown, M J I; Holwerda, B W; Wang, L
Abstract: We present a detailed analysis of the specific star formation rate–stellar mass (sSFR– M * ) of z ≤ 0.13 disc central galaxies using a morphologically selected mass-complete sample ( M * ≥ 10 9.5 M⊙ ). Considering samples of grouped and ungrouped galaxies, we find the sSFR– M * relations of disc-dominated central galaxies to have no detectable dependence on host dark-matter halo (DMH) mass, even where weak-lensing measurements indicate a difference in halo mass of a factor ≳ 5. We further detect a gradual evolution of the sSFR– M * relation of non-grouped (field) central disc galaxies with redshift, even over a Δ z ≈ 0.04 (≈5 × 10 8 yr) interval, while the scatter remains constant. This evolution is consistent with extrapolation of the 'main sequence of star-forming-galaxies' from previous literature that uses larger redshift baselines and coarser sampling. Taken together, our results present new constraints on the paradigm under which the SFR of galaxies is determined by a self-regulated balance between gas inflows and outflows, and consumption of gas by star formation in discs, with the inflow being determined by the product of the cosmological accretion rate and a fuelling efficiency – M_b, haloζ . In particular, maintaining the paradigm requires M_b, haloζ to be independent of the mass M halo of the host DMH. Furthermore, it requires the fuelling efficiency ζ to have a strong redshift dependence (∝(1 + z ) 2.7 for M * = 10 10.3 M⊙ over z = 0–0.13), even though no morphological transformation to spheroids can be invoked to explain this in our disc-dominated sample. The physical mechanisms capable of giving rise to such dependencies of ζ on M halo and z for discs are unclear.